2021
DOI: 10.3390/ijerph18116051
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Evolution of Network Structure and PrEP Adoption among a Large Cohort of PrEP Peer Leaders: Implications for Intervention Evaluation and Community Capacity-Building

Abstract: Background: Peer leader interventions are effective strategies for promoting prevention behaviors in communities at risk for HIV, yet little is known about their effects on the social and behavioral dynamics of peer leaders themselves. Methods: Using data from PrEP Chicago, an RCT PrEP for prevention intervention for young Black MSM (YBMSM), we apply stochastic actor-based models to longitudinally model the impact of study participation on the online friendship and PrEP adoption dynamics among a network of pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In addition, they have practice with taking a prescription daily and conversations of disclosure. Several studies among MSM demonstrated the desire for peer-matching based on identity considerations and lived experience to access PrEP, and that peer leaders with greater PrEP intentions and those living with HIV were more active in forming new friendships [ 36 , 37 ]. Thus, there is benefit to involving interested HIV-positive individuals in PrEP educational efforts and developing curricula specific to initiating conversation about PrEP with a sexual partner.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have practice with taking a prescription daily and conversations of disclosure. Several studies among MSM demonstrated the desire for peer-matching based on identity considerations and lived experience to access PrEP, and that peer leaders with greater PrEP intentions and those living with HIV were more active in forming new friendships [ 36 , 37 ]. Thus, there is benefit to involving interested HIV-positive individuals in PrEP educational efforts and developing curricula specific to initiating conversation about PrEP with a sexual partner.…”
Section: Discussionmentioning
confidence: 99%